Anabasine‐based measurement of cigarette consumption using wastewater analysis. Issue 9 (26th June 2020) - Bade, Richard; White, Jason M.; Tscharke, Benjamin J.; Ghetia, Maulik; Abdelaziz, Ahmed; Gerber, Cobus
Abstract: Community tobacco use can be monitored over time using wastewater‐based epidemiological approaches by estimating the mass loads of nicotine and its metabolites, cotinine, or hydroxycotinine, in wastewater. However, due to the use of nicotine in smoking cessation products, other sources of nicotine contribute to cotinine and hydroxycotinine loads. The use of nicotine replacement therapies could vary in space and time and mask the true rates of tobacco consumption. Therefore, this work evaluated the content of tobacco specific markers, anatabine and anabasine, in cigarettes, in urine of smokers, and in wastewater. The results indicated that the anabasine content in both licit and illicit cigarettes in Australia is less variable than anatabine and is therefore considered a better measure of tobacco consumption. A study determining the excretion of tobacco‐specific alkaloids of smoking and non‐smoking volunteers gave an average urinary mass load of anabasine of 4.38 μg/L/person and a daily mass load of 1.13 μg/day/person. Finally, this was compared with the mass loads of anabasine from wastewater‐based epidemiology data of 3 μg/day/person to estimate cigarette rates in a South Australian city: equivalent to 2.6 cigarettes/person/day. The rate of decline of cigarette use was greater when using anabasine as a measure of consumption compared with cotinine. This is the first study to estimate the rate of anabasine excretion, which can be used to estimate tobacco use independent of therapeutically prescribed nicotine. Abstract : This work analysed licit and illicit cigarettes in Australia and included a study determining the excretion of tobacco‐specific alkaloid is most suitable as a marker for tobacco smoking (i.e independent of nicotine‐containing smoking cessation pharmaceuticals). Anabasine was found to be the best marker and, for the first time, an excretion rate suitable for wastewater‐based epidemiology calculation was found.